Review of flow instability in gas-turbine compression system - Jingyi Zeng; Feng Liu (Propulsion and Power Research, 2025)
Compressor instability, particularly stall and surge, poses significant challenges to the performance, efficiency, and reliability of axial compressors in aerospace and power-generation systems. This review comprehensively summarizes the evolution of research on stall precursors, including modal wave, spike, rotating instability, and partial surge. Each precursor exhibits distinct spatial and temporal characteristics linked to specific unsteady flow structures such as tip leakage vortex breakdown, hub corner separation, and shock-boundary layer interactions. The transformation of stall precursors under varying design parameters and operating conditions is analyzed, with a focus on how radial loading distribution, tip clearance, and inlet distortion influence instability behavior. Future directions are proposed, emphasizing the development of unified theoretical models, accelerated numerical methods, and full-annulus experiments to enhance stall prediction and active control strategies.